Can't Stand up for Sitting Down - Brand, Jo (London Headline Review, 2010)
In the late 80s comedy was the new rock and roll and, now a full-time comedian, Jo s success on Friday Night Live landed her a primetime TV show of her own. She found herself in demand as an outspoken, funny commentator on life s foibles and silliness
Include Illustration
Keywords: Great Britain -- Comedians -- Brand, Jo